1974
DOI: 10.1530/acta.0.0760651
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Proteins and Hormone Synthesis in Human Thyroid Cancer

Abstract: Thyroid iodoproteins and hormone synthesis have been studied in vivo and in organ culture in 44 cases of thyroid cancer. In a few cases, Tg1) (17–19 S) is virtually absent; a portion of the light fractions (3–8 S), which seems to represent some precursors of Tg, incorporated in culture the 14C-amino acids. In most of the cases, the solubility profiles, sedimentation patterns as well as electrophoretic migration of proteins were normal. The content of Tg and the concentration of stable iodine (127I) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
16
0
1

Year Published

1984
1984
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 0 publications
6
16
0
1
Order By: Relevance
“…Our assay, therefore, likely underestimates cytotoxicity caused by 131 I. Most differentiated thyroid cancers have varying degrees of impaired iodide organification (53)(54)(55), but 131 I therapy is still effective in most thyroid cancer, even when organification is diminished or absent.…”
Section: Discussionmentioning
confidence: 96%
“…Our assay, therefore, likely underestimates cytotoxicity caused by 131 I. Most differentiated thyroid cancers have varying degrees of impaired iodide organification (53)(54)(55), but 131 I therapy is still effective in most thyroid cancer, even when organification is diminished or absent.…”
Section: Discussionmentioning
confidence: 96%
“…Although papillary and follicular thyroid carcinomas retain the majority of biological properties of normal thyroid cells, a variety of biochemical defects has been demonstrated (28)(29)(30). Indeed, impaired intrathyroidal iodine metabolism represents one of the most peculiar abnormalities present in thyroid neoplastic tissue.…”
Section: Alteration Of Iodine Metabolism In Cancer Tissuementioning
confidence: 99%
“…However, its concentration was lower than that in normal tissue and was lowest in poorly differentiated histotypes (8,13,14). In thyroid cancer tissue, Tg was poorly iodinated, and hormonal production of T 3 and T 4 was rarely observed (11,12,21). The present study suggests that its poor degree of iodination may be related to defects in both the iodine-trapping ability and the iodination process.…”
Section: Discussionmentioning
confidence: 49%
“…In in vitro studies, multiple biochemical abnormalities have been found, including a low intrathyroid concentration of iodine, a low degree of iodination of Tg, and a low rate of thyroid hormone synthesis (11,12). The biological activity of peroxidase, a key thyroid enzyme in the iodide organification process, although normal in benign cold adenomas, was decreased in thyroid carcinomas (10,15), whereas TSH-R were detected in most differentiated thyroid tumors, including thyroid carcinomas (8,14,19).…”
mentioning
confidence: 99%